2004
DOI: 10.2343/geochemj.38.1
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical studies of tektites from East Asia

Abstract: Thirty tektites from East Asia (including Wenchang and Penglei of Hainan Island, Maoming of Guandong, China; Khon-Kaen of Thailand; Bao Loc of Vietnam; Rizal of Luzon, Philippines) have been analyzed for major and trace element contents and Rb-Sr isotopic compositions. All the samples studied are splash form tektites. The trace element ratios Ba/Rb (avg. 3.74), Th/Sm (avg. 2.31), Sm/Sc (avg. 0.43), Th/Sc (avg. 0.99) and the rare earth elements (REE) contents of tektites studied are similar to the average upper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…Based on paleomagnetic studies, the Australasian tektite event appears to have taken place ϳ12-16 ka before the B/M reversal (Burns, 1989;Schneider et al, 1992;Lee and Wei, 2000), or ϳ0.8 Ma ago. This age is in agreement with the radiometric ages determined for the Australasian tektites (e.g., Izett and Obradovich, 1992;Kunz et al, 2000;Yamei et al, 2000;Lee et al, 2004). The Australasian strewn field covers nearly 10% of the Earth's surface.…”
Section: Introductionsupporting
confidence: 64%
“…Based on paleomagnetic studies, the Australasian tektite event appears to have taken place ϳ12-16 ka before the B/M reversal (Burns, 1989;Schneider et al, 1992;Lee and Wei, 2000), or ϳ0.8 Ma ago. This age is in agreement with the radiometric ages determined for the Australasian tektites (e.g., Izett and Obradovich, 1992;Kunz et al, 2000;Yamei et al, 2000;Lee et al, 2004). The Australasian strewn field covers nearly 10% of the Earth's surface.…”
Section: Introductionsupporting
confidence: 64%
“…The Nd model ages of the Transantarctic Mountain microtektites point to a dominantly Meso-Proterozoic (1.6-1.0 Ga) crustal source material. The Sr-Nd isotope composition for the Transantarctic Mountain microtektites has been compared to the literature data for the other tektite strewn fields (Compston and Chapman, 1969;Shaw and Wassenburg, 1982;Blum et al, 1992;Lee et al, 2004;Deutsch and Koeberl, 2006). In the e CHUR (Nd)-e UR (Sr) diagram (Fig.…”
Section: Sr and Nd Isotopic Compositionsmentioning
confidence: 99%
“…Figure 4 shows that there is a good correlation in the abundance of Rb, Mn, and Y between the tektite samples and the upper continental crust, but some trace elements are not closely correlated (i.e., Cr, Sr, Nb, and Ti). Many authors have used the CI-normalized ratios of the trace elements, such as Ba/Rb, Th/Sm, Th/Sc, Zr/Hf, and La/Lu to distinguish the provenance of tektites [10,11,13,23,28]. In Table 4, we list the CI-normalized ratios of Ba/Rb, Zr/Hf, and La/Lu for the southern China tektites, upper continental crust, low crust, oceanic crust, and primitive mantle.…”
Section: Southern China Tektitesmentioning
confidence: 99%
“…Many researchers suggested that potential impact site for Australasian strewn field was probably located in the region near the southern part of the Thailand-Laos border, indochina [12,18,23,45], and this area lies within a broad region of Mesozoic marine sedimentary rocks. The exact target rocks from which Australasian tektites were produced have not yet been identified.…”
Section: Mixing Model For Potential Target Materials Of the Southern Cmentioning
confidence: 99%
See 1 more Smart Citation